2014
DOI: 10.1063/1.4904349
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plasma frequency, damping constant, and size distribution from the complex dielectric function of noble metal nanoparticles

Abstract: Dependence of the localized surface plasmon resonance of noble metal quasispherical nanoparticles on their crystallinity-related morphologies This paper develops a novel method for simultaneously determining the plasma frequency x P and the damping constant c f ree in the bulk damped oscillator Drude model, based on experimentally measured real and imaginary parts of the metal refractive index in the IR wavelength range, lifting the usual approximation that restricts frequency values to the UV-deep UV region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…In this work we determine for the first time the Drude model parameters γ free and ω p for Ni, Mo, W, Pb, Zn and Na employing a method developed by Mendoza Herrera et al [26], which lifts the restriction free ω γ . It will be shown that the so obtained γ free and ω p allow a much more accurate fitting of the experimental bulk dielectric function discrete values in a wider wavelength range, beyond the visible and extending to the FIR depending of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we determine for the first time the Drude model parameters γ free and ω p for Ni, Mo, W, Pb, Zn and Na employing a method developed by Mendoza Herrera et al [26], which lifts the restriction free ω γ . It will be shown that the so obtained γ free and ω p allow a much more accurate fitting of the experimental bulk dielectric function discrete values in a wider wavelength range, beyond the visible and extending to the FIR depending of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…For nanoparticles, the scattering parameter has inherent contributions of the intrinsic properties of the material as well as from interface scattering, and therefore, it can be described as γ = γ bulk + γ scat . Interface scattering becomes significant when the effective electron path length L eff is larger than to the nanoparticle itself [31]. The effective path length for convex shapes particles, as sphere, rods, cubes etc, is expressed as L eff = 4V/S where V is the volume and S is the particle surface area [30].…”
Section: Resultsmentioning
confidence: 99%
“…Introducing the real ( ) and imaginary parts ( ), ̃ may be written as [25] ̃= + 26 The real part of refractive index of an ensemble consisting ZnO@M@Au spherical and cylindrical core shell embedded in host matrix which have dielectric function ℎ = 2.25 is analysed using Eq. (25) and (26). and 1000 .…”
Section: Refractive Indexmentioning
confidence: 99%
“…Decreasing the size of a nanoparticle will eventually cause the thickness to become less than the bulk mean free path, and electron scattering from the surfaces of the particle will have decreasing effect thus broadening its plasmon resonance peaks. If the electron mean free path depends on size of the nanoparticles, a correction is available for the nanoshells and in this case, can be modified to [26], [27], [28]…”
Section: Theoretical Model and Calculationmentioning
confidence: 99%